Determining the optimum mixture of three essential oils for potato sprout suppression at room temperature storage - Thoma, Jena L.; Cantrell, Charles L.; Tamang, Prabin; Zheljazkov, Valtcho D. (Frontiers in Plant Science, 2023)
As a staple crop, potatoes (Solanum tuberosum) play an important role in meeting daily caloric needs. To ensure adequate supplies for year-round consumption, potato quality must be maintained throughout lengthy storage periods. Towards this end, potato sprouting during storage must be minimized. Due to changing regulations regarding chemical means of potato sprout suppression, increased focus has turned to alternative products including essential oils (EO) as sprout suppressants in recent years. The complex composition of various EOs promises numerous options for sprout suppression. Furthermore, blends of several EOs may achieve enhanced sprout suppressant properties if synergistic interactions are present. We evaluated Syzygium aromaticum, Artemisia herba-alba, and Laurus nobilis EOs and blends thereof as sprout suppressants in potato cultivar Ranger Russet stored at room temperature and also tested for their antifungal activity against Colletotrichum fragariae, a causal organism of anthracnose disease in strawberries including other vegetables and fruits. A. herba-alba EO was an effective sprout suppressant when used alone and suppressed sprouting over the 90-day storage period. Interactions between A. herba-alba and S. aromaticum affected sprout length whereas interactions between A. herba-alba and L. nobilis EOs affected sprout number. An optimum blend of 50% - 82.31% A. herba-alba, 17.69% - 50% L. nobilis, and 0% - 1.01% S. aromaticum EOs could more effectively minimize tuber sprout length and number than any of the three whole EOs used alone. Among these three EOs, only S. aromaticum EO showed antifungal activity against C. fragariae in bioautography assay. These results exhibit the potential of EOs blends as a novel tactic in potato sprout suppression as well as potential natural product-based fungicides in managing C. fragariae.